Political Leaders' Discourses and Securitization of Migration: A Comparison of Turkey and the United States - Kabacaoglu, Selin; Memisoglu, Fulya (ILEM, 2021)
With the growing importance of human mobility in the global agenda since the early 1990s, international migration has increasingly evolved into a securitized phenomenon. This has also made international migrants a prominent target group of security speech acts. The main objective of this study is to explore migration-security nexus in the context of political discourses. The paper brings a comparative perspective to the role of political leader discourses in the securitization of migration by examining the cases of the United States (USA), hosting the largest number of international migrants, and Turkey, the world's top refugee hosting country. Through the analytical lens of critical discourse analysis (CDA) and securitization theory, the study unpacks the rhetoric used by Turkish President Recep Tayyip Erdogan and American President Donald John Trump towards migrants/ asylum seekers. As the key findings demonstrate, the way the two leaders reflect the migration-security relationship to their speech acts significantly varies. President Trump associates migrants with security issues in multiple ways including social, political and economic spheres, while President Erdogan's discourse links migrants with security issues in the economic realm, but his general discourse reflects a desecuritization approach. In both countries, it is observed that the discourses of political leaders concerning migrants and asylum seekers exert influence on public opinion.
Keywords: International migration; secularization; refugee; migrant; critical discourse analysis; COPENHAGEN-SCHOOL; CHANGING AGENDA; ASYLUM-SEEKERS; IMMIGRATION; SECURITY; CONSTRUCTION; NEWS; INTEGRATION; REFUGEES; ILLEGAL; Social Sciences - Other Topics